Abdominal Obesity and Association With Atherosclerosis Risk Factors: The Uberlândia Heart Study. Issue 11 (March 2016) - Roever, Leonardo S.; Resende, Elmiro. S.; Diniz, Angélica. L. D.; Penha-Silva, Nilson; Veloso, Fernando. C.; Casella-Filho, Antonio; Dourado, Paulo .M.M.; Chagas, Antonio .C.P.
Abstract : Abstract: Ectopic visceral fat (VF) and subcutaneous fat (SCF) are associated with cardiovascular risk factors. Gender differences in the correlations of cardiovascular disease risk factors and ectopic fat in the Brazilian population still lacking. Cross-sectional study with 101 volunteers (50.49% men; mean age 56.5 ± 18, range 19–74 years) drawn from the Uberlândia Heart Study underwent ultrasonography assessment of abdominal visceral adipose tissue with convex transducer of 3.5 MHz of frequency. The thickness of VF was ultrasonographically measured by the distance between the inner face of the abdominal muscle and the posterior face of abdominal aorta, 1 cm above the umbilicus. The SCF thickness was measured with a 7.5 MHz linear transducer transversely positioned 1 cm above the umbilical scar. The exams were always performed by the same examiner. Ectopic fat volumes were examined in relation to waist circumference, blood pressure, and metabolic risk factors. The VF was significantly associated with the levels of triglycerides ( P  < 0.01, r = 0.10), HDL cholesterol ( P  < 0.005, r = 0.15), total cholesterol ( P  < 0.01, r = 0.10), waist circumference ( P  < 0.0001, r = 0.43), systolic blood pressure ( P  < 0.001, r = 0.41), and diastolic blood pressure ( P  < 0.001, r = 0.32) in women, and with the levels of triglycerides ( P  < 0.002, r = 0, 14), HDL cholesterol ( P  < 0.032, r = 0.07), glucose ( P  < 0.001, r = 0.15), alanine aminotransferase (ALT) ( P  < 0.008, r = 0.12), gamma-GT ( P  < 0.001, r = 0.30), waist circumference ( P  < 0.001, r = 0.52), systolic blood pressure ( P  < 0.001, r = 0.32), and diastolic blood pressure ( P  < 0.001, r = 0.26) in men. SCF was significantly associated with the levels of triglycerides ( P  < 0.01, r = 0.34), LDL cholesterol ( P  < 0.001, r = 0.36), total cholesterol ( P  < 0.05, r = 0.36), waist circumference ( P  < 0.0001, r = 0.62), systolic and diastolic blood pressure ( P  < 0.05, r = 0.34) in women, and with the waist circumference ( P  < 0.001, r = 0.065)), and MetS ( P  < 0.05, r = 0.11) in men. The VF and SCF were correlated with most cardiovascular risk factors in both genders but our findings support the idea that there are gender differences in the correlations between ectopic fat deposition and the cardiovascular risk factors.